Social representations of injustice in sustainability transitions: the case of farmers and Dutch agricultural nitrogen policy - Upham, Paul; Scholte, Rianne; Feron, Sarah (Frontiers in Political Science, 2025)
Here we document publicly circulating social representations of farmers, including government policy proposals, in the context of the Dutch agricultural nitrogen controversy for the period 2019–2023. The data are articles in three different Dutch national newspapers. Our aim is to provide a social psychological account of what sociotechnical sustainability transition theorists describe as ‘regime resistance’, using an agricultural policy case. As these representations are principally of farmers as the victims of injustice, we use the lens of just transitions to further characterize and structure them. The main representations are of ongoing uncertainty for farmers; loss of sympathy for farmers; farmers not being listened to; difficulty in farmers engaging with what is perceived as a highly challenging governmental policy position; and a concern for the future of farming and farmers. The representations are further characterised by the emotion of anger. The approach adds to an understanding of the social psychology of resistance to policy-led ‘regime destabilisation’. Arguably, social representations associated with policy intended to effect sociotechnical change can be viewed as an indicator of the social condition of the transition and its key social groups.